MAKING APPLICATION FOR STUDENT ANIMATED PRIMARY PLANET USING MACROMEDIA FLASH 5.0 - Risdianto Risdianto; Ire Puspa Wardani, Skom, MMSi (Jurnal Sistem Informasi, 2005)
This explains the scientific writing program design motor credit payment transactionapplication using Visual Basic 6.0 programming language. In scientific writingdatabase is used also by using the program Active Data Object (ADO) which isintegrated in Visual Basic 6.0 program itself. Consists of four tables of consumers,collectors, credit and consumer installment. In the end application program forforeign currency transactions will be applied to the PT. Universal ODA to ease inperforming activities of motor credit payment transactions, such as creating a report.